2019
DOI: 10.5455/medarh.2019.73.23-27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients with Acute Myocardial Infarction According to Age

Abstract: Introduction: By development of the medicine, control of the risk factors for acute myocardial infarction (AMI), became the foundation of cardiology. Aim: To investigate the association of the age with presence of risk factors in patients with acute myocardial infarction. Methods: The study had a prospective, comparative and descriptive character, and it was done on a sample of 80 patients (n=80; 55 male and 25 female) Clinic for Heart, Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…AMI can have multiple etiology and complex physiological and pathological mechanisms, with the Framingham Heart Study identifying risk factors [ 24 ]. It has been reported that important risk factors of individuals with AMI include diabetes, inflammation, and aging, but age growth might not be controlled by external factors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMI can have multiple etiology and complex physiological and pathological mechanisms, with the Framingham Heart Study identifying risk factors [ 24 ]. It has been reported that important risk factors of individuals with AMI include diabetes, inflammation, and aging, but age growth might not be controlled by external factors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One important risk factor identified for coronary heart disease is diabetes, and it has been positively correlated with atherosclerosis onset and progression [ 24 ]. As a systemic metabolic disease, various vascular complications often occur during diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of this type of event has declined steadily over the last decades, it still affects about 7 million individuals around the world annually, of which many occur in Europe, with the economic issues it entails 3 . Risk factors for MI include male gender, smoking, arterial hypertension, dyslipidemia, Diabetes mellitus, and obesity, among others 1,4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 Risk factors for MI include male gender, smoking, arterial hypertension, dyslipidemia, Diabetes mellitus, and obesity, among others. 1,4,5 MI can have different causes and be characterized in very different ways. One of the most used classifications is based on the presence of an elevation of the ST-segment in the electrocardiogram (ECG), thus allowing us to categorize the event as acute MI with ST-segment elevation (STEMI) or without ST-segment elevation (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the prevalence of acute myocardial infarction (AMI) has been gradually rising. AMI is the myocardial necrosis caused by acute myocardial ischemia, and it is mainly on the grounds of coronary artery diseases [ 1 ]. The clinical features include persistent and severe retrosternal pain, elevated serum myocardial enzymes and white blood cell counts, fever, arrhythmia, progressive electrocardiographic changes, heart failure, and even shock [ 2 ].…”
Section: Introductionmentioning
confidence: 99%